2017
DOI: 10.1002/cbf.3283
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of microRNAs in TM3 Leydig cells of mice treated with brain‐derived neurotrophic factor

Abstract: Brain-derived neurotrophic factor (BDNF) is a neurotrophin that can promote the development and proliferation of neurons. BDNF has been found to be involved in male reproduction. Leydig cells in testicular interstitial tissues can secrete testosterone in a luteinizing hormone-dependent manner. We showed that BDNF and its receptor TrkB were expressed in mice TM3 Leydig cells in the present study. Furthermore, BDNF can promote proliferation of mouse TM3 Leydig cells in vitro. Results of microRNA (miRNA) deep seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Elucidating the mechanism of ZEN toxicity to humans and animals is of great clinical significance to prevent and treat ZEN. Recent studies have shown that the addition of reproductive hormones to TM3 cells affects the expression of miRNAs in TM3 Leydig cells [17]. Therefore, we speculate that miRNAs are involved in the regulation of ZEN toxicology after ZEN is exposed to TM3 cells.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Elucidating the mechanism of ZEN toxicity to humans and animals is of great clinical significance to prevent and treat ZEN. Recent studies have shown that the addition of reproductive hormones to TM3 cells affects the expression of miRNAs in TM3 Leydig cells [17]. Therefore, we speculate that miRNAs are involved in the regulation of ZEN toxicology after ZEN is exposed to TM3 cells.…”
Section: Discussionmentioning
confidence: 80%
“…The miRNA maturation process involved in the nuclear processing of primary miRNA by DROSHA, nuclear export of precursor miRNA (pre- miRNA) by exportin 5, and cytoplasmic processing of pre- miRNA by DICER [15]. Recent studies showed that the differential expression of miRNAs in mouse Leydig cells was discovered by the addition of the brain-derived neurotrophic factor and luteinizing hormone during the cultivation of TM3 cells [16,17]. These studies show that miRNAs may be involved in the regulation of hormones in certain physiological functions of mouse Leydig cells.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a bioinformatics analysis of the small RNA sequencing results identified several miRNAs that were differentially regulated in the cortices of 1-month-old NexKO mice compared to controls ( Figure 2 A–I). Most of these miRNAs were previously linked to brain development, such as miR-10b-5p [ 87 , 89 ], miR-145a-5p [ 90 ], miR-221-5p [ 91 ], miR-29c-5p [ 92 ], miR-186-5p [ 93 ], miR-34b-5p [ 94 ], and miR-34c-5p [ 94 ].…”
Section: Resultsmentioning
confidence: 99%
“…To examine this possibility, we utilized next-generation sequencing (NGS) techniques, which revealed considerable alterations in the expression levels of several miRNAs of interest in NexKO mice compared to controls. Among these were several miRNAs that were previously linked to brain development, such as miR-10b-5p [ 87 , 89 ], miR-145a-5p [ 90 ], miR-221-5p [ 91 ], miR-29c-5p [ 92 ], miR-186-5p [ 93 ], miR-34b-5p [ 94 ], and miR-34c-5p [ 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…ZEA and its metabolites have structural analogy to estrogen, thus they can bind to estrogen receptors (ERs) and exert the estrogen-like effects [41]. Recent studies have shown that the addition of reproductive hormones including estrogen could affect the expression of miRNAs in TM3 Leydig cells [42]. Furthermore, study has clearly shown that oxidative stress can be a regulator of miRNAs, and can affect the expression of Micro-RNAs [43].…”
Section: Discussionmentioning
confidence: 99%